2022
DOI: 10.1371/journal.pone.0264226
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive health risk assessment of microbial indoor air quality in microenvironments

Abstract: The higher airborne microbial concentration in indoor areas might be responsible for the adverse indoor air quality, which relates well with poor respiratory and general health effects in the form of Sick building syndromes. The current study aimed to isolate and characterize the seasonal (winter and spring) levels of culturable bio-aerosols from indoor air, implicating human health by using an epidemiological health survey. Microorganisms were identified by standard macro and microbiological methods, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…In healthcare settings, this may concur with a higher level of skin exposure that may facilitate the translocation of skin bacteria to the air. However, studies from different settings also indicate high levels of Staphylococcus in the air (34). Further comparative studies could demonstrate if healthcare settings air microbiota is more close to human skin microbiota than other settings.…”
Section: Discussionmentioning
confidence: 96%
“…In healthcare settings, this may concur with a higher level of skin exposure that may facilitate the translocation of skin bacteria to the air. However, studies from different settings also indicate high levels of Staphylococcus in the air (34). Further comparative studies could demonstrate if healthcare settings air microbiota is more close to human skin microbiota than other settings.…”
Section: Discussionmentioning
confidence: 96%
“…Other traditional methods and techniques 4 , 6 , 17 , 43 47 , such as biological air and dust samplings, culture-based analysis, morphology techniques, and microbial volatile organic compound (VOC) measurements 48 51 , were used to evaluate the levels of molds and bacteria measured in indoor and outdoor environments, including residential dwellings (households), daycare centers, kindergartens, schools, and elderly care centers. However, many previous studies reported several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…they are also quite common in indoor air [e.g. 48,49], the process of their sedimentation removal from the air may have played a key role in contamination of the examined surfaces. Among isolated filamentous fungi and cocci, a number of microorganisms have cellulolytic properties (Tab.…”
Section: Aaem Annals Of Agricultural and Environmental Medicinementioning
confidence: 99%